Use of angle-resolved photoemission and density functional theory for surface structural analysis of YSi2 - Koitzsch, Christian; Bovet, M.; Garnier, Michael Bernard Gunnar; Aebi, Philipp; Rogero, C.; Martín-Gago, J. A. (My University, 2004)
The atomic structure of two-dimensional yttrium silicide epitaxially grown on Si(1 1 1) was investigated by means of density functional theory calculations and angle-resolved photoemission experiments. The obtained accuracy of the calculations allowed to discriminate different surface arrangements in a quantitative way via comparing their theoretical band structure to the experimental result. Theoretically we find significant changes in the dispersion of a surface localized band upon varying the thickness of the topmost silicon bilayer. For a thickness of 0.4 Å of the topmost silicon bilayer a strong asymmetry of the surface localized band with respect to ‾Γ is found, while a thickness of 0.8 Å yields a more symmetric dispersion of the band. By comparison with the experimental photoemission results, which show a rather symmetric band around ‾Γ, we can conclude that the topmost bilayer has a thickness of 0.8 Å.
Keywords: density functional calculations; angle resolved photoemission; surface electronic phenomena (work function; surface potential; surface states; etc.); surface structure; morphology; roughness; and topography; metal–semiconductor interfaces; yttrium; silicon